2024
DOI: 10.3390/agronomy14020289
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Biostimulants in the Improvement of Extended Storage Quality of In Vitro-Derived Plants of Popular Ornamental Perennials

Natalia Miler,
Alicja Tymoszuk,
Anita Woźny
et al.

Abstract: In vitro propagation is a crucial method for the mass production of high-quality plants, but the impact of microbiological interventions during ex vitro storage remains an underexplored aspect. This study aims to assess the effects of three commercial biostimulants in the form of microbiological preparations—BactoFungiStop, AzotoPower, and Guard—applied over six months through foliar sprays on the post-storage quality of Brunnera macrophylla ‘Silver Heart’, Echinacea purpurea ‘Secret Glow’, Heuchera × hybrida … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…Akensous and colleagues [ 32 ] have studied plant growth-promoting rhizobacteria (PGPR) and biostimulants extracted from compost materials that can increase drought tolerance or morphological traits [ 33 ]. The latter effects have been described in several herbaceous ornamental plant species grown in containers [ 34 ]. Zhang in his study [ 35 ] found that Festuca arundinacea , also used as an ornamental plant, enhances the defensive response to heat stress through lipid conversion.…”
Section: Introductionmentioning
confidence: 99%
“…Akensous and colleagues [ 32 ] have studied plant growth-promoting rhizobacteria (PGPR) and biostimulants extracted from compost materials that can increase drought tolerance or morphological traits [ 33 ]. The latter effects have been described in several herbaceous ornamental plant species grown in containers [ 34 ]. Zhang in his study [ 35 ] found that Festuca arundinacea , also used as an ornamental plant, enhances the defensive response to heat stress through lipid conversion.…”
Section: Introductionmentioning
confidence: 99%